Telaah Prinsip Jual Beli dalam Perspektif Al Qur’an (Kajian Analisis Q.S. An Nisā’ Ayat 29): PRINSIP JUAL BELI DALAM AL QURAN (Kajian Ananlisis Q.S An-Nisa’ ayat 29) - Dainuri Dainuri; Tika Diliana; Laila Murningsih Novrian Wakhidah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
One of the important muamalah activities in the daily lives of Muslims is buying and selling. Islam provides clear and strong guidelines regarding the principles to be followed in every transaction involving buying and selling, as outlined in the Quran and Hadith. The views of the commentators regarding buying and selling in Surah An-Nisa, verse 29, are interesting to examine. Why does Allah refer to the parable of the Arab society of ignorance in the past? It is possible that this parable represents a reality that exists and remains unchanged today. Therefore, it is crucial that Allah discusses buying and selling and its status. Buying and selling transactions truly play a vital role in human life. They provide a means for people to meet each other's needs. The existence of buying and selling activities also demonstrates that humans are social creatures who require the involvement of other humans to fulfill their needs. Nowadays, the buying and selling of goods in sacks is commonplace in society. This system, in which prospective buyers cannot directly inspect the condition and quality of the goods they wish to purchase, raises questions regarding their validity under Sharia law. The purpose of this study is to analyze the compliance of these transactions with the principles of Sharia law, particularly regarding the contract, honesty, and willingness of both parties.